A CaAl2Si2-Type Magnetic Semiconductor (Sr, Na)(Zn, Mn)2Sb2 Isostructural to 122-Type Iron-Based Superconductors - Yilun Gu; Rufei Zhang; Haojie Zhang; Licheng Fu; Guoxiang Zhi; Jinou Dong; Xueqin Zhao; Lingfeng Xie; Fanlong Ning (Advances in Condensed Matter Physics)
A new diluted magnetic semiconductor (Sr, Na)(Zn, Mn)2Sb2 has been successfully synthesized by doping Na and Mn into the parent compound SrZn2Sb2, which has a CaAl2Si2-type crystal structure (space group P3¯m1, No. 164, hP5) isostructural to the 122-type iron-based superconductor CaFe2As2. No magnetic ordering has been observed when only spins are doped by (Zn, Mn) substitution. Only with carriers codoped by (Sr, Na) substitution, a ferromagnetic ordering occurs below the maximum Curie temperature TC∼9.5 K. Comparing with other CaAl2Si2-type diluted magnetic semiconductors, we will show that negative chemical pressure suppresses the Curie temperature.